Optical glass and optical element

By optimizing the composition of optical glass, reducing the content of Gd2O3 and adding other high-efficiency components, the high-cost problem in the existing technology is solved, and optical glass with high refractive index and low cost is achieved, which is suitable for the manufacturing of optical components.

CN119330586APending Publication Date: 2025-01-21HOYA OPTICAL TECH (WEIHAI) CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310901608.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, in order to achieve high refractive index glass, glass containing Gd2O3 is often used, but due to the high unit price of Gd2O3, the glass cost is high, making it difficult to achieve lower cost.

Method used

By optimizing the composition of the glass, reducing the content of Gd2O3, and increasing the content of other ingredients such as La2O3, Y2O3, ZnO, etc., we ensure that the refractive index of the glass is high and the cost is low. The specific composition includes SiO2, B2O3, La2O3, Y2O3, ZnO, ZrO2, Nb2O5, etc. The molar ratio of each component is reasonably adjusted to achieve the goals of high refractive index and low cost.

Benefits of technology

Optical glass with low Gd2O3 content and high refractive index has been realized, which reduces the production cost of the glass while ensuring the high performance of the optical glass and is suitable for the manufacturing of optical components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004353978890000151
    Figure BDA0004353978890000151
  • Figure BDA0004353978890000161
    Figure BDA0004353978890000161
  • Figure BDA0004353978890000171
    Figure BDA0004353978890000171
Patent Text Reader

Abstract

The present invention relates to an optical glass and an optical element, in a glass composition represented by mol% on an oxide basis, the content of SiO2 is 0.00% to 30.00%, the content of B2O3 is 30.00% to 80.00%, the content of La2O3 is 8.00% to 40.00%, the content of Gd2O3 is 0.00% to 3.00%, the content of Y2O3 is 2.00% to 10.50%, the content of ZnO is 1.00% to 20.00%, the content of ZrO2 is 0.00% to 15.00%, and the balance is glass. The content of Nb2O5 is from 0.40% to 5.00% (inclusive), the content of TiO2 is from 0.00% to 3.00% (inclusive), the content of SrO is from 0.00% to 1.00% (inclusive), and the total content of La2O3, Y2O3 and ZnO (La2O3 + Y2O3 + ZnO) is 27.40% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to optical glass and optical elements. Background Art

[0002] In recent years, optical glass having a high refractive index has been proposed as a material for optical elements (see, for example, Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2002-128539 Summary of the invention

[0006] Problems to be solved by the invention

[0007] In Patent Document 1 (Japanese Patent Publication No. 2002-128539), a glass composition containing a large amount of Gd2O3 is disclosed as a glass composition for achieving a high refractive index (refer to the examples in Japanese Patent Publication No. 2002-128539). However, since Gd2O3 is an expensive component with a high unit price in recent years, a glass with a low Gd2O3 content is preferred for reducing the cost of glass.

[0008] In view of the above, one object of the present invention is to provide an optical glass with a low Gd2O3 content and a high refractive index.

[0009] Technical solutions to solve problems

[0010] An aspect of the present invention is as follows.

[0011] [1] An optical glass, wherein, in a glass composition expressed in mol % on an oxide basis,

[0012] The SiO2 content is 0.00% or more and 30.00% or less,

[0013] The B2O3 content is 30.00% or more and 80.00% or less,

[0014] The La2O3 content is 8.00% or more and 40.00% or less,

[0015] The Gd2O3 content is 0.00% or more and 3.00% or less,

[0016] The Y2O3 content is 2.00% or more and 10.50% or less,

[0017] The ZnO content is 1.00% or more and 20.00% or less,

[0018] The ZrO2 content is 0.00% or more and 15.00% or less,

[0019] The Nb2O5 content is 0.40% or more and 5.00% or less,

[0020] The TiO2 content is 0.00% or more and 3.00% or less,

[0021] The SrO content is 0.00% or more and 1.00% or less, and

[0022] The total content of La2O3, Y2O3 and ZnO (La2O3+Y2O3+ZnO) is more than 27.40%.

[0023] [2] The optical glass according to [1], wherein the total content of SiO2 and B2O3 (SiO2+B2O3) is 56.80% or more and 63.44% or less.

[0024] [3] The optical glass as described in [1] or [2], wherein the total content of ZrO2 and Nb2O5 (ZrO2+Nb2O5) is greater than 0.40% and less than 9.80%.

[0025] [4] The optical glass according to any one of [1] to [3], wherein the total content of ZrO2 and Nb2O5 (ZrO2+Nb2O5) is 7.93% or more and 9.80% or less.

[0026] [5] The optical glass according to any one of [1] to [4], wherein the molar ratio of the La2O3 content to the Y2O3 content (La2O3 / Y2O3) is greater than or equal to 2.20 and less than or equal to 4.15.

[0027] [6] The optical glass according to any one of [1] to [5], wherein the molar ratio of the La2O3 content to the Y2O3 content (La2O3 / Y2O3) is 2.345 or more and 3.46 or less.

[0028] [7] In the optical glass described in any one of [1] to [6], the molar ratio of the total content of SiO2 and B2O3 to the total content of La2O3, Gd2O3 and Y2O3 ((SiO2+B2O3) / (La2O3+Gd2O3+Y2O3)) is greater than 2.20 and less than 2.59.

[0029] [8] In the optical glass described in any one of [1] to [7], the molar ratio of the total content of SiO2 and B2O3 to the total content of Nb2O5, TiO2 and WO3 (SiO2+B2O3) / (Nb2O5+TiO2+WO3) is greater than 31.10.

[0030] [9] In the optical glass described in any one of [1] to [8], the molar ratio of the total content of SiO2 and B2O3 to the total content of Nb2O5, TiO2 and WO3 (SiO2+B2O3) / (Nb2O5+TiO2+WO3) is greater than 31.10 and less than 88.50.

[0031]

[10] In the optical glass described in any one of [1] to [9], the molar ratio of the total content of ZnO and Y2O3 to the content of Nb2O5 ((ZnO+Y2O3) / Nb2O5) is greater than 5.00 and less than 18.00.

[0032]

[11] The optical glass according to any one of [1] to

[10] , wherein the total content of SiO2 and B2O3 (SiO2+B2O3) is 56.80% or more and 63.44% or less,

[0033] The total content of ZrO2 and Nb2O5 (ZrO2+Nb2O5) is 7.93% or more and 9.80% or less,

[0034] The molar ratio of La2O3 content to Y2O3 content (La2O3 / Y2O3) is 2.345 or more and 3.46 or less,

[0035] The molar ratio of the total content of SiO2 and B2O3 to the total content of La2O3, Gd2O3 and Y2O3 ((SiO2+B2O3) / (La2O3+Gd2O3+Y2O3)) is 2.20 or more and 2.59 or less,

[0036] The molar ratio of the total content of SiO2 and B2O3 to the total content of Nb2O5, TiO2 and WO3 (SiO2+B2O3) / (Nb2O5+TiO2+WO3) is 31.10 or more and 88.50 or less, and

[0037] The molar ratio of the total content of ZnO and Y2O3 to the content of Nb2O5 ((ZnO+Y2O3) / Nb2O5) is 5.00 or more and 18.00 or less.

[0038]

[12] An optical element comprising the optical glass according to any one of [1] to

[11] .

[0039] Effects of the Invention

[0040] According to one aspect of the present invention, an optical glass having a low Gd2O3 content and a high refractive index and an optical element composed of the optical glass can be provided. DETAILED DESCRIPTION

[0041] [Optical glass]

[0042] In the present invention and this specification, the glass composition of the optical glass is expressed as a glass composition based on oxides expressed in mol%. Here, the so-called "glass composition based on oxides" refers to a glass composition obtained by completely decomposing glass raw materials during melting and converting them into glass compositions existing as oxides in the glass. In the glass composition expressed in mol%, the glass composition is expressed on a molar basis (mol%, molar ratio). Hereinafter, for the glass composition expressed in mol%, "mol%" is also abbreviated as "%".

[0043] In the present invention and this specification, the content of a constituent component of 0%, 0.0% or 0.00%, or not contained or not introduced, means that the constituent component is substantially not contained, and the content of the constituent component is below the impurity level. Below the impurity level means, for example, less than 0.01%. "0%" can mean, for example, "0.0%" or "0.00%". The content of a certain component of "more than 0%, "more than 0.0%" or "more than 0.00%" means that the component is an arbitrary component.

[0044] The glass composition in the present invention and this specification can be obtained by methods such as ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). For example, quantitative analysis is performed on each element using ICP-AES. Then, the analysis value is converted into oxides and recorded. The analysis value based on ICP-AES, for example, contains a measurement error of about ±5% of the analysis value. Therefore, the value recorded for the oxide after conversion based on the analysis value also contains an error of about ±5%.

[0045] In the present invention and this specification, the refractive index refers to the refractive index nd of the d-line (wavelength 587.56 nm) of helium.

[0046] In the present invention and this specification, the Abbe number νd is used as a value indicating a property related to dispersion and is represented by the following formula.

[0047] νd=(nd-1) / (nF-nC)

[0048] In the above formula, nF is the refractive index of the F line (wavelength 486.13 nm) of blue hydrogen, and nC is the refractive index of the C line (656.27 nm) of red hydrogen.

[0049] Hereinafter, the above optical glass (may be simply described as “glass”) will be described in more detail.

[0050] <Glass Composition>

[0051] The SiO2 content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. SiO2 is a glass network component, and when its content decreases, there is a tendency for the viscosity of the glass to decrease and the formability to decrease. From the above viewpoints, the SiO2 content is preferably 0.50% or more, and more preferably 1.00% or more, 1.50% or more, 2.00% or more, 2.50% or more, 3.00% or more, 3.50% or more, and 4.00% or more.

[0052] On the other hand, when SiO2 content increases, the solubility and refractive index of glass tend to decrease. From the above viewpoint, SiO2 content is 30.00% or less, preferably 28.00% or less, and more preferably 26.00% or less, 24.00% or less, and 22.00% or less in sequence.

[0053] B2O3 is a glass network component and also a component that lowers the melting temperature of glass. When the B2O3 content decreases, the glass stability tends to decrease due to the lack of glass network components. From the above viewpoints, the B2O3 content is 30.00% or more, preferably 32.00% or more, and more preferably 34.00% or more, 36.00% or more, 38.00% or more, and 40.00% or more.

[0054] On the other hand, when the content of B2O3 increases, the influence of volatilization becomes greater. Therefore, from the viewpoint of ease of control of optical properties, the content of B2O3 is 80.00% or less, preferably 75.00% or less, and more preferably 70.00% or less, 65.00% or less, and 60.00% or less, respectively.

[0055] From the viewpoint of improving the stability of the glass, the total content of SiO2 and B2O3 (SiO2+B2O3) is preferably 56.80% or more, more preferably 57.00% or more, and further preferably 57.50% or more, 58.00% or more, 58.50% or more, 59.00% or more, and 60.00% or more, respectively.

[0056] On the other hand, from the viewpoint of suppressing the decrease in the refractive index of the glass, the total content (SiO2+B2O3) is preferably less than 63.44%, more preferably less than 63.30%, and further preferably less than 63.10%, less than 62.90%, less than 62.70%, and less than 62.60%, respectively.

[0057] La2O3 is a component that contributes to high refractive index and low dispersion of glass. The La2O3 content is 8.00% or more, preferably 9.00% or more, and more preferably 10.00% or more, 11.00% or more, 12.00% or more, 13.00% or more, 14.00% or more, 15.00% or more, 16.00% or more, and 17.00% or more.

[0058] On the other hand, when the La2O3 content increases, the glass tends to be highly dispersed, easily devitrified, and has a higher specific gravity. From the above viewpoints, the La2O3 content is 40.00% or less, preferably 35.00% or less, and more preferably 30.00% or less, 25.00% or less, and 21.00% or less.

[0059] The content of Gd2O3 is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. The content of Gd2O3 is a component that contributes to the high refractive index and low dispersion of the glass. However, Gd2O3 is a component with a high unit price and a large specific gravity, so when it is contained in the glass, it is preferably contained in as small an amount as possible. The content of Gd2O3 is 3.00% or less, preferably 2.50% or less, and more preferably 2.00% or less, 1.50% or less, 1.00% or less, 0.50% or less, and preferably 0.00%.

[0060] Y2O3 is a component that contributes to high refractive index and low dispersion of glass. The Y2O3 content is 2.00% or more, preferably 2.50% or more, and more preferably 3.00% or more, 3.50% or more, 4.00% or more, 4.50% or more, 5.00% or more, 5.50% or more, and 6.00% or more.

[0061] On the other hand, when the Y2O3 content increases, the glass tends to be highly dispersed and easily devitrified. From the above viewpoints, the Y2O3 content is 10.50% or less, preferably 10.00% or less, and more preferably 9.00% or less and 8.00% or less.

[0062] From the viewpoint of suppressing glass crystallization, the molar ratio of the La 2 O 3 content to the Y 2 O 3 content (La 2 O 3 / Y 2 O 3) is 2.20 or more and 4.15 or less.

[0063] From the viewpoint of inhibiting glass crystallization, the molar ratio of La2O3 content to Y2O3 content (La2O3 / Y2O3) is preferably 2.20 or more, more preferably 2.30 or more, 2.31 or more, 2.32 or more, 2.33 or more, 2.34 or more, or 2.345 or more.

[0064] In addition, from the viewpoint of inhibiting glass crystallization, the molar ratio (La2O3 / Y2O3) is preferably 4.15 or less, and more preferably 4.00 or less, 3.80 or less, 3.60 or less, 3.46 or less, 3.40 or less, and 3.20 or less, respectively.

[0065] From the viewpoint of improving the stability of the glass, the molar ratio of the total content of SiO2 and B2O3 to the total content of La2O3, Gd2O3 and Y2O3 (((SiO2+B2O3) / (La2O3+Gd2O3+Y2O3)) is preferably above 2.20, and more preferably above 2.21, above 2.22, above 2.23, above 2.24, above 2.25, above 2.26 and above 2.27, respectively.

[0066] On the other hand, from the viewpoint of suppressing the decrease in the refractive index of glass, the molar ratio (SiO2+B2O3) / (La2O3+Gd2O3+Y2O3) is preferably below 2.59, and more preferably below 2.57, below 2.55, below 2.53, below 2.51, below 2.49, below 2.47, and below 2.46, respectively.

[0067] ZnO is a component that lowers the glass transition temperature Tg. The ZnO content is 1.00% or more, preferably 1.05% or more, and more preferably 1.10% or more, 1.15% or more, 1.20% or more, 1.25% or more, and 1.30% or more.

[0068] On the other hand, when the ZnO content increases, the glass is easily crystallized and the stability of the glass is easily reduced. From the above viewpoints, the ZnO content is 20.00% or less, preferably 18.00% or less, and more preferably 16.00% or less, 14.00% or less, 12.00% or less, 10.00% or less, 8.00% or less, and 7.00% or less.

[0069] From the viewpoint of low dispersion of glass, the total content of La2O3, Y2O3 and ZnO (La2O3+Y2O3+ZnO) is 27.40% or more, preferably 27.50% or more, more preferably 27.60% or more, and 27.70% or more. The total content (La2O3+Y2O3+ZnO) can be, for example, 40.00% or less, 39.00% or less, 38.00% or less, 37.00% or less, 36.00% or less, 35.00% or less, 34.00% or less, or 33.00% or less.

[0070] The ZrO2 content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. ZrO2 is a component that contributes to the high refractive index and low dispersion of glass. The ZrO2 content is preferably 1.00% or more, and more preferably 2.00% or more, 3.00% or more, 4.00% or more, 5.00% or more, and 6.00% or more.

[0071] On the other hand, when the ZrO2 content increases, there is a tendency for the solubility of the glass to decrease. From the viewpoint of maintaining the solubility of the glass, the ZrO2 content is 15.00% or less, preferably 14.00% or less, and more preferably 13.00% or less, 12.00% or less, 11.00% or less, 10.00% or less, and 9.00% or less.

[0072] From the viewpoint of improving the high refractive index, low dispersion and stability of the glass, the Nb2O5 content is above 0.40%, preferably above 0.45%, and more preferably above 0.50%, above 0.55%, above 0.60%, above 0.65% and above 0.70%, respectively.

[0073] On the other hand, when the Nb2O5 content increases, the solubility of the glass tends to decrease, and the Abbe number νd also tends to decrease. Therefore, from the viewpoint of maintaining the solubility of the glass and reducing the dispersion, the Nb2O5 content is 5.00% or less, preferably 4.50% or less, and more preferably 4.00% or less, 3.50% or less, 3.00% or less, 2.50% or less, and 2.00% or less.

[0074] From the viewpoint of high refractive index and low dispersion of glass, the total content of ZrO2 and Nb2O5 (ZrO2 + Nb2O5) is preferably above 0.40%, and more preferably above 0.50%, above 1.00%, above 1.50%, above 2.00%, above 2.50%, above 3.00%, above 3.50%, above 4.00%, above 4.50%, above 5.00%, above 5.50%, above 6.00%, above 6.50%, above 7.00%, above 7.50%, above 7.70%, above 7.80%, above 7.90%, and above 7.93%.

[0075] On the other hand, from the viewpoint of inhibiting the crystallization of glass, the total content (ZrO2+Nb2O5) is preferably 9.80% or less, preferably 9.70% or less, and more preferably 9.60% or less, 9.50% or less, 9.40% or less, and 9.30% or less, respectively.

[0076] Regarding the molar ratio of the total content of ZnO and Y2O3 to the content of Nb2O5 (((ZnO+Y2O3) / Nb2O5), if the value of the molar ratio is small, the Abbe number νd value tends to become larger, and if the value of the molar ratio is large, the Abbe number νd value tends to become smaller. From the viewpoint of controlling the Abbe number νd within the desired range as a material for optical elements, the molar ratio ((ZnO+Y2O3) / Nb2O5) is preferably greater than 5.00, and more preferably greater than 5.20, greater than 5.40, greater than 5.60, greater than 5.80, and greater than 6.00, respectively.

[0077] In addition, from the above viewpoints, the molar ratio (ZnO+Y2O3) / Nb2O5) is preferably 18.0 or less, and more preferably 17.00 or less and 16.00 or less, respectively.

[0078] The TiO2 content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. TiO2 is a component that contributes to the high refractive index and low dispersion of glass. However, it is a component that reduces the transmittance of glass. From the viewpoint of suppressing the decrease in the transmittance of glass, the TiO2 content is 3.00% or less, preferably 2.00% or less, more preferably 1.00% or less, further preferably 0.50% or less, and best 0.00%.

[0079] Regarding the molar ratio of the total content of SiO2 and B2O3 to the total content of Nb2O5, TiO2 and WO3 (SiO2+B2O3) / (Nb2O5+TiO2+WO3), when the value of this molar ratio becomes larger, the glass tends to have high dispersion, and when the value of this molar ratio becomes smaller, the glass tends to have low dispersion. From the viewpoint of controlling the Abbe number νd within the desired range as a material for optical elements, the molar ratio (SiO2+B2O3) / (Nb2O5+TiO2+WO3) is preferably 31.10 or more, and more preferably 32.00 or more, 33.00 or more, 34.00 or more, 35.00 or more, and 36.00 or more, respectively.

[0080] The molar ratio (((SiO2+B2O3) / (Nb2O5+TiO2+WO3)) can be, for example, 120.00 or less, 110.00 or less, 100.00 or less, 98.00 or less, 96.00 or less, 94.00 or less, 92.00 or less, 90.00 or less, 89.00 or less, or 88.50 or less.

[0081] In the above glass, the contents of WO3 and Bi2O3 are each 0.00% or more, and may be 0.00% or more.

[0082] WO3 and Bi2O3 are components that contribute to giving the glass a high refractive index and low dispersion. By making the respective contents below 2.00%, it is possible to suppress the reduction in the transmittance of the glass to ultraviolet to visible light (especially wavelengths below 500nm). From this point of view, the respective contents of WO3 and Bi2O3 are preferably below 2.00%, more preferably below 1.50%, below 1.00%, below 0.50%, and most preferably 0.00%.

[0083] SrO is a component that contributes to a high refractive index and low dispersion of glass. The SrO content is 0.00% or more, and may be 0.00%, 0.00% or more, or more than 0.00%.

[0084] When the SrO content increases, the glass tends to devitrify easily. Therefore, from the viewpoint of maintaining glass stability, the SrO content is 1.00% or less, preferably 0.90% or less, and more preferably 0.80% or less, 0.70% or less, 0.60% or less, and 0.50% or less.

[0085] The content of each of MgO, CaO and BaO is 0.00% or more, and may be 0.00% or more. From the viewpoint of suppressing glass devitrification and achieving desired optical properties, the content of each of MgO, CaO and BaO is preferably 5.00% or less, more preferably 4.00% or less, and further preferably 3.00% or less, 2.00% or less, and 1.00% or less, respectively.

[0086] The Li2O content is 0.00% or more, and may be 0.00% or more. From the viewpoint of further improving the thermal stability of the glass, suppressing the decrease in the glass transition temperature (thereby improving the machinability), and improving the chemical durability and weather resistance, the Li2O content is preferably 5.00% or less, and more preferably 4.00% or less, 3.00% or less, and 2.00% or less, respectively.

[0087] The content of each of Na2O, K2O, Rb2O and Cs2O is 0.00% or more, and may be 0.00% or more. Na2O, K2O, Rb2O and Cs2O all have the effect of improving the melting property of glass, but when their content increases, the thermal stability, chemical durability, weather resistance and machinability of glass tend to decrease. Therefore, the content of each of Na2O, K2O, Rb2O and Cs2O is preferably 5.00% or less, and more preferably 4.00% or less, 3.00% or less, and 2.00% or less, respectively.

[0088] For other glass components, the Al2O3 content may be 0.00%, 0.00% or more, or more than 0.00%. In addition, the Al2O3 content may be, for example, 5.00% or less, 4.00% or less, 3.00% or less, or 2.00% or less.

[0089] Regarding other glass components, considering the environmental impact, the As2O3 content is preferably 0.10% or less, more preferably 0.01% or less, and most preferably 0.00%. In addition, considering the environmental impact, the PbO content is preferably 1.00% or less, more preferably 0.50% or less, 0.10% or less, and most preferably 0.00%.

[0090] Ta2O5 is an expensive component. From the viewpoint of reducing the cost of glass, the Ta2O5 content is preferably 2.00% or less, more preferably 1.50% or less, 1.00% or less, 0.50% or less, and most preferably 0.00%.

[0091] Sb2O3 is a component that can be added as a clarifier. A small amount of addition can also play a role in suppressing the reduction of light transmittance caused by the mixing of impurities such as Fe, but if the amount of Sb2O3 added is increased, the coloring of the glass tends to increase. Therefore, the amount of Sb2O3 added is preferably 0.00% or more and 0.10% or less, more preferably 0.00% or more and 0.08% or less, and further preferably 0.00% or more and 0.05% or less. The Sb2O3 content based on the external ratio refers to the Sb2O3 content expressed in mass % when the total content of the glass components other than Sb2O3 is set to 100 mass %.

[0092] SnO2 can also be added as a clarifier, but if it is added in excess of 1.00% in an external ratio, Sn becomes the starting point for nucleation and produces a tendency to devitrification when the glass is colored, or when the glass is heated and softened for re-forming such as press forming. Therefore, the amount of SnO2 added is preferably 0.00% or more and 1.00% or less, more preferably 0.00% or more and 0.50% or less, and preferably not added. The SnO2 content based on the external ratio refers to the content of SnO2 expressed in mass % when the total content of the glass components other than SnO2 is set to 100 mass %.

[0093] <Glass Properties>

[0094] (Refractive index nd)

[0095] The glass may be a high refractive index glass by having the glass composition. From the viewpoint of usefulness as a material for an optical element, the refractive index nd of the glass is preferably 1.7860 or more, more preferably 1.7861 or more, and further preferably 1.7862 or more, 1.7863 or more, 1.7864 or more, 1.7865 or more, 1.7866 or more, 1.7867 or more, 1.7868 or more, 1.7869 or more, 1.7870 or more, 1.7871 or more, 1.7872 or more, 1.7873 or more, 1.7874 or more, and 1.7875 or more.

[0096] In addition, from the viewpoint of usefulness as a material for optical elements, the refractive index nd of the above-mentioned glass is preferably less than 1.7935, more preferably less than 1.7934, and further preferably less than 1.7933, less than 1.7932, less than 1.7931, less than 1.7930, less than 1.7929, less than 1.7928, less than 1.7927, less than 1.7926, less than 1.7925, less than 1.7924, less than 1.7923, and less than 1.7922, respectively.

[0097] (Abbe number νd)

[0098] The glass can show low dispersion by having the glass composition. From the viewpoint of usefulness as a material for optical elements, the Abbe number νd of the glass is preferably 48.50 or less, more preferably 48.45 or less, and further preferably 48.40 or less, 48.35 or less, 48.30 or less, 48.25 or less, 48.20 or less, 48.15 or less, 48.10 or less, and 48.05 or less.

[0099] In addition, from the perspective of usefulness as a material for optical elements, the Abbe number νd of the above-mentioned glass is preferably greater than 46.50, more preferably greater than 46.60, and further preferably greater than 46.70, greater than 46.80, greater than 46.90, greater than 47.00, greater than 47.10, greater than 47.20, and greater than 47.30, respectively.

[0100] (proportion)

[0101] In the optical element constituting the optical system, the refractive power is determined by the refractive index of the glass constituting the optical element and the curvature of the optical functional surface (the surface where the light entering and exiting the optical element is to be controlled). When the curvature of the optical functional surface is to be increased, the thickness of the optical element is also increased. As a result, the optical element becomes heavier. In contrast, if a glass with a high refractive index is used, a large refractive power can be obtained even without increasing the curvature of the optical functional surface.

[0102] As described above, if the refractive index can be increased while suppressing an increase in the specific gravity of glass, it is possible to reduce the weight of an optical element having a certain refractive power.

[0103] From the above viewpoints, the specific gravity of the above-mentioned glass is preferably less than 5.00, more preferably less than 4.95, and more preferably less than 4.90, less than 4.85, less than 4.80, less than 4.75, less than 4.70, less than 4.65, less than 4.60, and less than 4.55. The lower the specific gravity, the more preferred it is from the viewpoint of lightweight optical elements, so the specific gravity of the above-mentioned glass is not particularly limited to a lower limit. In one embodiment, the specific gravity of the above-mentioned glass can be, for example, more than 4.00, more than 4.05, more than 4.10, more than 4.15, more than 4.20, or more than 4.25. In the present invention and this specification, "specific gravity" is a value measured by the Archimedean method.

[0104] (Coloring degree λ5, λ 80 )

[0105] The light transmittance of glass, in detail, the suppression of the light absorption end on the short wavelength side from the longer wavelength can be controlled by the coloring degree λ5 and λ 80 The coloration degree λ5 represents the wavelength at which the spectral transmittance (including surface reflection loss) of glass with a thickness of 10±0.1mm from the ultraviolet region to the visible region is 5%. 80 The wavelength at which the spectral transmittance is 80% as measured by the method described for λ5. 80 It is a value measured in the wavelength range of 250 to 700 nm. For the spectral transmittance T (%) of the glass in the present invention and this specification, the intensity of light incident perpendicularly on one side of the two parallel planes of a glass sample having two planes parallel to each other after optical polishing is set as I in , the intensity of the light emitted from the other side through the glass sample is set to I out When , it is expressed as follows.

[0106] T(%)=I out / I in ×100

[0107] According to the chromaticity λ5 and λ 80 , the absorption end on the short wavelength side of the spectral transmittance can be quantitatively evaluated. For example, when lenses are bonded together using an ultraviolet curing adhesive to make a bonded lens, the adhesive is irradiated with ultraviolet light through an optical element to cure the adhesive. From the perspective of efficiently curing the ultraviolet curing adhesive, it is preferred that the absorption end on the short wavelength side of the spectral transmittance is in the short wavelength region. As an indicator for quantitatively evaluating the absorption end on the short wavelength side, the coloring degree λ5 and λ 80One or more of the.

[0108] The above-mentioned glass can preferably represent a λ5 of 330nm or less. λ5 is more preferably 329nm or less, 328nm or less, 327nm or less, 326nm or less, 325nm or less, 324nm or less, 323nm or less, 322nm or less, 321nm or less, 320nm or less, 319nm or less, 318nm or less, and 317nm or less. The shorter the wavelength of λ5, the more preferred it is, and the lower limit is not particularly limited. In one embodiment, λ5 can be 300nm or more, 301nm or more, 302nm or more, 303nm or more, or 304nm or more.

[0109] The glass is preferably capable of expressing a wavelength of λ below 410 nm. 80 . 80 More preferably, the wavelength is 409 nm or less, 408 nm or less, 407 nm or less, 406 nm or less, 405 nm or less, 404 nm or less, 403 nm or less, 402 nm or less, 401 nm or less, and 400 nm or less. 80 The shorter the wavelength, the more preferred it is, and there is no particular lower limit. 80 It may be 380 nm or more, 381 nm or more, 382 nm or more, 383 nm or more, 384 nm or more, or 385 nm or more.

[0110] (Glass transition temperature Tg)

[0111] From the viewpoint of machinability (specifically, the viewpoint that the glass is not easily broken during mechanical processing such as cutting, cutting, grinding and polishing), the glass transition temperature Tg of the above-mentioned glass is preferably above 640°C, and more preferably above 645°C, above 650°C, above 655°C and above 660°C, respectively.

[0112] On the other hand, from the viewpoint of reducing the burden on the annealing furnace or the forming mold, the glass transition temperature Tg of the above-mentioned glass is preferably below 750°C, and more preferably below 745°C, below 740°C, below 735°C, below 730°C, and below 725°C, respectively.

[0113] The glass transition temperature Tg was determined using a differential scanning calorimeter at a temperature increase rate of 10° C. / min.

[0114] <Method for producing optical glass>

[0115] In order to obtain the target glass composition, the above optical glass is prepared by weighing and blending oxides, carbonates, sulfates, nitrates, hydroxides, etc. as raw materials, fully mixing them as a mixed batch, heating and melting them in a melting container, degassing and stirring them, and making a homogeneous and bubble-free molten glass, which can be obtained by shaping it. Specifically, it can be made using a known melting method.

[0116] [Glass material for press molding, optical element blank, and method for producing the same]

[0117] Another aspect of the present invention relates to a press-molding glass material composed of the above optical glass; and an optical element blank composed of the above optical glass.

[0118] According to another embodiment of the present invention, there is also provided a method for manufacturing a glass raw material for stamping molding, which comprises the step of forming the above-mentioned optical glass into a glass raw material for stamping molding; a method for manufacturing an optical element blank, which comprises the step of making an optical element blank by stamping the above-mentioned glass raw material for stamping molding of the optical glass using a stamping mold; and a method for manufacturing an optical element blank, which comprises the step of forming the above-mentioned optical glass into an optical element blank.

[0119] The so-called optical element blank is an optical element base material that is similar to the shape of the target optical element, and the grinding amount (surface layer removed by grinding) and the grinding amount (surface layer removed by grinding) as required are added to the shape of the optical element. The optical element is completed by grinding and polishing the surface of the optical element blank. In one method, the optical element blank can be made by a method (called direct stamping method) of stamping and forming molten glass obtained by melting the above-mentioned glass in an appropriate amount. In another method, the optical element blank can also be made by solidifying the molten glass obtained by melting the above-mentioned glass in an appropriate amount.

[0120] In another embodiment, an optical element blank can be produced by preparing a press-molding glass material and press-molding the prepared press-molding glass material.

[0121] The press-forming of the glass raw material for press forming can be performed by a known method of using a press-forming die to press the glass raw material for press forming in a heated and softened state. Both the heating and the press-forming can be performed in the atmosphere. By annealing after the press-forming to reduce the deformation inside the glass, a homogeneous optical element blank can be obtained.

[0122] In addition to materials called glass blocks for press forming (gobs) used for press forming of optical element blanks in their original state, press forming glass raw materials also include materials that are subjected to mechanical processing such as cutting, grinding, and polishing and are used for press forming via glass blocks for press forming. As a cutting method, there are methods of forming a groove in the portion to be cut on the surface of the glass plate by a method called scribing, applying local pressure to the groove portion from the back of the groove-forming surface, and cutting the glass plate at the groove portion, or a method of cutting the glass plate using a cutting blade, etc. In addition, as grinding and polishing methods, drum grinding, etc. can be cited.

[0123] The glass raw material for press forming can be produced, for example, by casting molten glass into a casting mold to form a glass plate, and cutting the glass plate into a plurality of glass sheets. Alternatively, a suitable amount of molten glass can be formed to produce a glass block for press forming. The optical element blank can also be produced by reheating, softening and press forming the glass block for press forming. The method of reheating, softening and press forming the glass to produce the optical element blank is called a reheating press method relative to the direct press method.

[0124] [Optical element and method of manufacturing the same]

[0125] Another aspect of the present invention relates to an optical element composed of the above optical glass.

[0126] The optical element is made of the optical glass. In the optical element, one or more layers of coatings such as multilayer films such as anti-reflection films may be formed on the glass surface.

[0127] According to one aspect of the present invention, there is also provided a method for producing an optical element, comprising the step of producing an optical element by grinding and / or polishing the optical element blank.

[0128] In the manufacturing method of the above optical element, mechanical processing such as grinding and lapping can be performed by a known method, and an optical element with high internal quality and surface quality can be obtained by fully cleaning and drying the surface of the optical element after processing. In this way, an optical element composed of the above optical glass can be obtained. As the optical element, various lenses such as spherical lenses, aspherical lenses, micro lenses, prisms, etc. can be exemplified.

[0129] In addition, the optical element composed of the above optical glass is also suitable as a lens constituting a joined optical element. As a joined optical element, there can be exemplified an element formed by joining lenses to each other (joined lens), an element formed by joining a lens and a prism, and the like. For example, a joined optical element can be made by precision machining the joining surfaces of the two joined optical elements (for example, spherical grinding) so that the shape becomes an inverted shape, applying an ultraviolet curing adhesive for bonding the joined lenses and bonding them, and then irradiating ultraviolet rays through the lens to cure the adhesive, thereby making it. In order to make a joined optical element in this way, the above optical glass is preferred. By using a plurality of glasses with different Abbe numbers νd to respectively make a plurality of joined optical elements and joining them, it is possible to make an element suitable for chromatic aberration correction.

[0130] [Example]

[0131] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to the embodiments shown in the examples.

[0132] [Example 1]

[0133] <No.1~156>

[0134] Nitrates, sulfates, carbonates, hydroxides, oxides, boric acid, etc. corresponding to the raw materials for introducing the respective components are weighed and sufficiently mixed to obtain the glass composition (unit: mol %) shown in the following table.

[0135] The blended raw materials were placed in a platinum crucible, heated and melted in a furnace set at 1350°C for 2 hours. After the molten glass was stirred and homogenized, the molten glass was poured into a preheated mold, cooled to near the glass transition temperature, and immediately placed in an annealing furnace, kept at a temperature around the glass transition temperature for about 30 minutes, and then slowly cooled at a slow cooling rate of -30°C / hour for 4 hours, and then cooled in the furnace to room temperature, to obtain the optical glasses No. 1 to 156 shown in the following table.

[0136] The Sb2O3 contents shown in the following table are contents expressed as a percentage (unit: mass %).

[0137] The physical properties of the optical glass obtained in this way are shown in the following table.

[0138] Various physical properties of the optical glass were measured by the methods shown below.

[0139] <Evaluation of Physical Properties of Optical Glass>

[0140] (1) Refractive index nd Abbe number νd

[0141] The refractive index nd and the Abbe number νd of the obtained glass were measured by a refractive index measurement method in accordance with the standards of the Japan Optical Glass Industries Association.

[0142] (2) Glass transition temperature Tg

[0143] The glass was fully pulverized in a mortar as a sample, and the glass transition temperature Tg was measured using a differential scanning calorimeter (DSC8271) manufactured by Rigaku Corporation at a heating rate of 10° C. / min using a platinum cell as a sample container.

[0144] (3) Specific gravity

[0145] Determine specific gravity by Archimedes method.

[0146] (4) Coloring degree λ5, λ 80

[0147] A glass sample with a thickness of 10±0.1 mm and two optically polished surfaces facing each other was used to measure the spectral transmittance T (%) by a spectrophotometer. The wavelength (nm) at which T is 5% is λ5, and the wavelength (nm) at which T is 80% is λ 80 .

[0148]

Table 1

[0149]

[0150]

[0151]

[0152]

[0153]

[0154]

[0155]

[0156]

[0157] [Example 2]

[0158] The various glasses obtained in Example 1 were used to prepare glass blocks for press molding (glass blocks). The glass blocks were heated and softened in the atmosphere, and were press molded using a press mold to prepare lens blanks (optical element blanks). The prepared lens blanks were taken out of the press mold, annealed, and subjected to mechanical processing including grinding to prepare spherical lenses composed of the various glasses prepared in Example 1.

[0159] [Example 3]

[0160] The molten glass prepared in Example 1 is pressed in a desired amount using a press forming die to prepare a lens blank (optical element blank). The prepared lens blank is taken out from the press forming die, annealed, and subjected to mechanical processing including grinding to prepare a spherical lens composed of the various glasses prepared in Example 1.

[0161] [Example 4]

[0162] The glass block (optical element blank) produced by solidifying the molten glass produced in Example 1 was annealed and subjected to mechanical processing including grinding, thereby producing spherical lenses composed of the various glasses produced in Example 1.

[0163] [Example 5]

[0164] The spherical lens produced in Examples 2 to 4 is bonded to a spherical lens made of other types of glass to produce a joined lens. The bonding surface of the spherical lens produced in Examples 2 to 4 is a convex surface, and the bonding surface of the spherical lens made of other types of glass is a concave surface. The two bonding surfaces are produced in such a way that the absolute values ​​of the radii of curvature are equal to each other. An ultraviolet curing adhesive for bonding optical elements is applied to the bonding surface, and the two lenses are bonded to each other on the bonding surface. Then, the adhesive applied on the bonding surface is irradiated with ultraviolet rays through the spherical lens produced in Examples 2 to 4 to cure the adhesive.

[0165] The cemented lens was manufactured as described above. The cemented lens had a sufficiently high bonding strength and a sufficient level of optical performance.

[0166] The embodiments disclosed this time should be considered as illustrative in all aspects and not restrictive. The scope of the present invention is indicated by the claims rather than the above description, and the purpose is to include all modifications within the meaning and scope equivalent to the claims.

[0167] For example, by adjusting the composition described in the specification to the glass composition exemplified above, the optical glass of one embodiment of the present invention can be obtained.

[0168] Furthermore, it is of course possible to arbitrarily combine two or more items described as examples or preferred ranges in the specification.

Claims

1. An optical glass, wherein: In the glass composition expressed in mol% on an oxide basis, The SiO2 content is 0.00% or more and 30.00% or less, The B2O3 content is 30.00% or more and 80.00% or less, The La2O3 content is 8.00% or more and 40.00% or less, The Gd2O3 content is 0.00% or more and 3.00% or less, The Y2O3 content is 2.00% or more and 10.50% or less, The ZnO content is 1.00% or more and 20.00% or less, The ZrO2 content is 0.00% or more and 15.00% or less, The Nb2O5 content is 0.40% or more and 5.00% or less, The TiO2 content is 0.00% or more and 3.00% or less, The SrO content is 0.00% or more and 1.00% or less, and The total content of La2O3, Y2O3 and ZnO (La2O3+Y2O3+ZnO) is more than 27.40%.

2. The optical glass according to claim 1, wherein: The total content of SiO2 and B2O3 (SiO2+B2O3) is greater than or equal to 56.80% and less than or equal to 63.44%.

3. The optical glass according to claim 1, wherein: The total content of ZrO2 and Nb2O5 (ZrO2+Nb2O5) is greater than or equal to 0.40% and less than or equal to 9.80%.

4. The optical glass according to claim 1, wherein: The total content of ZrO2 and Nb2O5 (ZrO2+Nb2O5) is greater than or equal to 7.93% and less than or equal to 9.80%.

5. The optical glass according to claim 1, wherein: The molar ratio of the La2O3 content to the Y2O3 content (La2O3 / Y2O3) is 2.20 or more and 4.15 or less.

6. The optical glass according to claim 1, wherein: The molar ratio of the La2O3 content to the Y2O3 content (La2O3 / Y2O3) is 2.345 or more and 3.46 or less.

7. The optical glass according to claim 1, wherein: The molar ratio of the total content of SiO2 and B2O3 to the total content of La2O3, Gd2O3 and Y2O3 ((SiO2+B2O3) / (La2O3+Gd2O3+Y2O3)) is greater than or equal to 2.20 and less than or equal to 2.

59.

8. The optical glass according to claim 1, wherein: The molar ratio of the total content of SiO2 and B2O3 to the total content of Nb2O5, TiO2 and WO3 (SiO2+B2O3) / (Nb2O5+TiO2+WO3) is greater than 31.

10.

9. The optical glass according to claim 1, wherein: The molar ratio of the total content of SiO2 and B2O3 to the total content of Nb2O5, TiO2 and WO3 (SiO2+B2O3) / (Nb2O5+TiO2+WO3) is greater than or equal to 31.10 and less than or equal to 88.

50.

10. The optical glass according to claim 1, wherein: The molar ratio of the total content of ZnO and Y2O3 to the content of Nb2O5 ((ZnO+Y2O3) / Nb2O5) is 5.00 or more and 18.00 or less.

11. The optical glass according to claim 1, wherein: The total content of SiO2 and B2O3 (SiO2+B2O3) is 56.80% or more and 63.44% or less, The total content of ZrO2 and Nb2O5 (ZrO2+Nb2O5) is greater than or equal to 7.93% and less than or equal to 9.80%. The molar ratio of La2O3 content to Y2O3 content (La2O3 / Y2O3) is 2.345 or more and 3.46 or less, The molar ratio of the total content of SiO2 and B2O3 to the total content of La2O3, Gd2O3 and Y2O3 ((SiO2+B2O3) / (La2O3+Gd2O3+Y2O3)) is 2.20 or more and 2.59 or less, The molar ratio of the total content of SiO2 and B2O3 to the total content of Nb2O5, TiO2 and WO3 (SiO2+B2O3) / (Nb2O5+TiO2+WO3) is 31.10 or more and 88.50 or less, and The molar ratio of the total content of ZnO and Y2O3 to the content of Nb2O5 ((ZnO+Y2O3) / Nb2O5) is 5.00 or more and 18.00 or less.

12. An optical element, wherein: The optical glass is composed of any one of claims 1 to 11.

Citation Information

Patent Citations

  • Low fluorescent optical glass

    JP2002128539A